Éthique du corps et enjeux contemporains du sacré dans la réflexion du cheikh Sa‘îd Ramaḍân al-Bûṭî - Sandra Houot (Revue des Mondes Musulmans et de la Méditerranée)
In this paper, we would like to stress the contemporary bringing to the fore of the body as seen as sacred through the magistry of the Syrian shaykh S.R al-Bûṭî and its proceeding stakes. At first, we set an ideal background, owing to its normative and naturalizing bound, which casts for this ‘âlim an ethical framework. Afterwards, with some al-Buti personal legal advices (fatâwâ) we will examine the present experience of the sacred reflected by the body, underlain by ethics.